High Performance Imaging Using Large Camera Arrays - Wilburn, Bennett; Joshi, Neel; Vaish, Vaibhav; Talvala, Eino-Ville; Antunez, Emilio; Barth, Adam; Adams, Andrew; Horowitz, Mark; Levoy, Marc (SIGGRAPH '05 ACM SIGGRAPH 2005 Papers, 2005)
The advent of inexpensive digital image sensors, and the ability to create photographs that combine information from a number of sensed images, is changing the way we think about photography. In this paper, we describe a unique array of 100 custom video cameras that we have built, and we summarize our experiences using this array in a range of imaging applications. Our goal was to explore the capabilities of a system that would be inexpensive to produce in the future. With this in mind, we used simple cameras, lenses, and mountings, and we assumed that processing large numbers of images would eventually be easy and cheap. The applications we have explored include approximating a conventional single center of projection video camera with high performance along one or more axes, such as resolution, dynamic range, frame rate, and/or large aperture, and using multiple cameras to approximate a video camera with a large synthetic aperture. This permits us to capture a video light field, to which we can apply spatiotemporal view interpolation algorithms in order to digitally simulate time dilation and camera motion. It also permits us to create video sequences using custom non-uniform synthetic apertures.